Hardcore Twenty-Four - Evanovich, Janet; King, Lorelei (New York, New York : Penguin Random House, 2017)
Events take a dark turn when headless bodies start appearing across town. At first it's just corpses from a funeral home and the morgue that have had the heads removed. But when a homeless man is murdered, Stephanie Plum knows that she's the only one with a prayer of catching this killer.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women detectives -- Fiction; Women bounty hunters -- Fiction; Murder -- Fiction -- Investigation; Trenton (N.J.) -- Fiction; Audiobooks; Detective and mystery fiction